Cardiovascular manifestations of aluminium phosphide intoxication - Singh, R B; Rastogi, S S; Singh, D S (Journal of the Association of Physicians of India, 1989)
Aluminium phosphide (ALP) a major suicidal agent in the developing countries is freely available as grain fumigant. It is highly toxic to lungs, heart and blood vessels causing pulmonary oedema, shock and arrhythmias. There is massive focal myocardial damage resulting in raised cardiac enzymes. Clinical manifestations were nausea and vomiting (32), dyspnoea and palpitations (25 each), cyanosis (12), hypotension (12) and shock (15). Cardiac arrhythmias were present in 28 cases and hypermagnesaemia in 13 patients. Mean serum magnesium level (1.95 +/- 0.2O, mEq/L) was significantly raised compared to mean magnesium level in control subjects (1.62 +/- 0.23 mEq/L). Hypermagnesaemia occurs due to myocardial and liver damage. Out of 32 cases studied, 22 died 18 within 24 hours of ALP ingestion. Thirty two cases of ALP were studied.